Predictors of weight loss in HIV-infected women on antiretroviral therapy in Rwanda. - Kimenyi, Jean Paul (My University, 2014)
Background: Highly Active Antiretroviral Treatment (HAART) has reduced the frequency of weight loss/wasting associated with HIV infection. However, weight loss remains a problem, even in the HAART era. Objectives: This study was carried out to assess weight change in a cohort of HIV-infected women on HAART in Rwanda, from 2005 to 2008, and to identify factors that predict weight loss in this cohort. Methods: Data from a cohort of 449 HIV-positive women on HAART enrolled in the Rwanda Women’s Inter-association Study and Assessment (RWISA), starting in May 2005, and followed at six monthly intervals until December 2008, were analysed. The outcome assessed in this study was change in weight, measured in kilograms at 6, 12 and 24 months after HAART initiation. Nutritional status was recorded and laboratory measurements (weight, height and CD4 cell count) were taken prior and after HAART initiation. All covariates were time dependent, except for the history of weight loss which was recorded at baseline only. Generalized Estimating Equation (GEE) using the linear link (Gaussian [normal]), exchangeable covariance structure and robust standard error was used to assess the factors associated with changes in weight (weight loss or weight gain) and to control for potential confounders. Results: Prior to HAART initiation, the mean weight of the study participants was 53.1 kg (SD 9.5). The mean BMI was 21.3 kg/m2 (SD 3.6) and the mean CD4 cell count was 222.9 cells/μL (SD 120.6) [47.6% had CD4 cell counts <200 cells/μL, 52.2% had CD4 cell counts ≥200 cells/μL]. Overall, the participants gained weight from baseline to 12 months after HAART initiation. The mean weight change was 1.9 kg (SD 7.8) (p<0.001) 6 months after HAART initiation, 2.9 kg (SD 5.9) (p <0.001) 12 months after HAART initiation, and 2.4 kg (SD 6.5) (p <0.001) 24 months after HAART initiation. Six months after HAART initiation, 48.3% of participants had gained weight, and 21.0% had lost weight. Twelve months after HAART initiation, 56.9% had gained weight, and 18.3% had lost weight, Twenty-four months after HAART initiation, 56.6% had gained weight, and 22.6% had lost weight. Participants with CD4 cell counts ≤ 200 cells/μL at baseline gained more weight than those with CD4 cell counts > 200 cells/μL at 6, 12 and 24 months after HAART initiation. Participants who were underweight (BMI <18.5 kg/m2) at baseline gained more weight than other participants three months after HAART initiation. Time-dependent diarrhoea for more than two weeks and a CD4 cell count of 200 - 350 cells/μL were significantly associated with weight loss (p≤ 0.05). Others factors, such as time-dependent education level (completion of secondary school), marital status (married legally and status other than married legally or widowed), and increases in CD4 cell counts, were associated with weight gain (p≤ 0.05). Conclusion: Although the majority of participants gained weight during the first 12 months of being on HAART, a significant proportion of participants lost weight while on HAART. The findings on the predictors of weight change in HIV-positive women on HAART can be used to promote weight gain in women who start HAART. Clinicians who take care of HIV-infected patients on HAART should pay attention to those who lose weight, and those who present with diarrhoea or with CD4 cell counts of <350 cells/μL at follow-up visits, since these factors are associated with weight loss in the HAART era.
Keywords: Rwanda; women; HAART; HIV/AIDS; weight loss; weight gain; wasting; longitudinal study; secondary data; Weight Loss; Antiretroviral Therapy, Highly Active; HIV-1--drug effects